Manajemen Pembiayaan dalam Meningkatkan Mutu Pendidikan - Romlah; Novarita, Herni; Imansyah, M. Aditiya; Megawati; Ria Pusvita, Mega (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Improving the quality of education depends not only on the size of the available budget, but also on the effectiveness of the financing management applied by educational institutions. This study aims to analyze the implementation of financial management in enhancing educational quality within private religious-based institutions, with a case study at MTs Al-Hidayah Sukajaya, Bandar Lampung. A qualitative approach was employed using a case study design. Data were collected through participatory observation, in-depth interviews, and document analysis, and analyzed thematically using Miles and Huberman’s interactive model. The results indicate that MTs Al-Hidayah implements need-based budgeting, transparent and accountable financial execution, and continuous oversight through internal audits and participatory evaluation. These strategies have proven effective in increasing public trust, improving infrastructure quality, and enhancing teacher motivation and performance. The study implies that participatory, need-based, and accountable financial management is essential to achieving sustainable educational quality, particularly in resource-constrained madrasah.